The Role of Treponema denticola Motility in Synergistic Biofilm Formation With Porphyromonas gingivalis - Ng, Hong Min (Front Cell Infect Microbiol, 2019)
Chronic periodontitis has a polymicrobial biofilm etiology and interactions between key oral bacterial species, such as Porphyromonas gingivalis and Treponema denticola contribute to disease progression. P. gingivalis and T. denticola are co-localized in subgingival plaque and have been previously shown to exhibit strong synergy in growth, biofilm formation and virulence in an animal model of disease. The motility of T. denticola, although not considered as a classic virulence factor, may be involved in synergistic biofilm development between P. gingivalis and T. denticola. We determined the role of T. denticola motility in polymicrobial biofilm development using an optimized transformation protocol to produce two T. denticola mutants targeting the motility machinery. These deletion mutants were non-motile and lacked the gene encoding the flagellar hook protein of the periplasmic flagella (ΔflgE) or a component of the stator motor that drives the flagella (ΔmotB). The specificity of these gene deletions was determined by whole genome sequencing. Quantitative proteomic analyses of mutant strains revealed that the specific inactivation of the motility-associated gene, motB, had effects beyond motility. There were 64 and 326 proteins that changed in abundance in the ΔflgE and ΔmotB mutants, respectively. In the ΔflgE mutant, motility-associated proteins showed the most significant change in abundance confirming the phenotype change for the mutant was related to motility. However, the inactivation of motB as well as stopping motility also upregulated cellular stress responses in the mutant indicating pleiotropic effects of the mutation. T. denticola wild-type and P. gingivalis displayed synergistic biofilm development with a 2-fold higher biomass of the dual-species biofilms than the sum of the monospecies biofilms. Inactivation of T. denticola flgE and motB reduced this synergy. A 5-fold reduction in dual-species biofilm biomass was found with the motility-specific ΔflgE mutant suggesting that T. denticola periplasmic flagella are essential in synergistic biofilm formation with P. gingivalis.